Evaluasi Pelaksanaan Penilaian Autentik (Aspek Psikomotorik) Dalam Pembelajaran Berkarya Seni Rupa Dua Dimensi (Studi Pada Sekolah Menengah Atas Di Kecamatan Pattallassang Kabupaten Takalar) - Irwan, Irwan; Jayadi, Karta; Yunus, Pangeran Paita (Universitas Negeri Makassar, 2018)
The study aims at discovering (1) the result of Fine Arts teachers’ knowledge at senior high schools in Pattallassang subdistrict of Takalar district which referred to Permendikbud No.23/2016 on Standard of Education Assessment and Assessment Guidance of Esthetics Subject, (2) the result of the implementation of learning assessment included the planning, implementation, utilization, and assessment report, and (3) the result of the implementation of authentic assessment (psychomotor aspect) in Two Dimensional Fine Arts learning in grade XII at senior high schools in Pattallassang subdistrict of Takalar district. The type of this study was evaluation research with descriptive qualitative approach. The evaluation model used was Stake Countenance Model. The study was conducted from the 5th February to 5th March, 2018 at senior high school in Pattallassang subdistrict of Takalar district. The subjects of the study were teachers of Fine Arts. Data were collected by employing questionnaire, interview, and documentation. Data were analyzed descriptively. The results of the study reveal that (1) there are still teachers of Fine Arts subject art senior high schools in Pattallassang subdistrict of Takalar district who did not acknowledge and understand Permendikbud No.23/2016 due to lack of socialization by related parties such as Education Office and Head of education unit, and lack of assessment training for teachers of Fine Arts subject, (2) administratively, teachers of Fine Arts subject at senior high schools in Pattallassang subdistrict of Takalar district had set assessment plan program and conducted assessmet, but had not fully referred to Permendikbud No.23/2016, (3) learning result assessment conducted by teachers of Fine Arts subject at senior high schools in Pattallassang subdistrict of Takalar district was generally an assessment merely to meet educational unit so the implementation of assessment principle standard was not conducted as expected.